(untitled) (Texas Journal of Medical Science, 2022)
The analysis of the safety and efficacy of anesthetic treatments in obese patients with recurrent ventral hernias has been carried out. Patients undergoing treatment in the departments of general surgery and surgical diseases No. There were 70 obese patients with recurrent ventral hernias aged 18 to 60 years. All patients were divided into 2 groups: the first main group of 40 patients who received general anesthesia in combination with epidural anesthesia. The second control group consisted of 30 patients who received multicomponent general anesthesia.